Surgical Repair of Open Achilles Tendon Injuries Using No.1 Prolene to Pull Down the Proximal Tendon: A Safe Technique (TAJ: Journal of Teachers Association, 2009)
From July 1998 to October 2004 forty-seven patients with open tendo-Achilles injuries were treated pull down the proximal tendon with no.1 prolene. In this surgical method no.1 prolene was threaded through the proximal tendon and the same suture material passed through the distal tendon and its bilateral ends were tightened over the rubber button either under the heel or by the sides of the heel. Box sutures apposed cut ends of the tendon. The ankle was placed in the cast in near neutral position. At six weeks the cast was removed and active flexion program was started. Partial weight bearing was allowed at seven weeks and full bearing was allowed at ten weeks after surgery. The average follow up period is 1.8 years. All the patients exhibited full range of motion at the final follow-up. doi: 10.3329/taj.v21i2.3792 TAJ 2008; 21(2): 132-134